2011
DOI: 10.1016/j.molimm.2011.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Complement mediated apoptosis leads to the loss of retinal ganglion cells in animal model of glaucoma

Abstract: This study investigated the role of complement in the protection of retinal ganglion cells (RGCs) in chronic ocular hypertension model of glaucoma. Intraocular pressure (IOP) was elevated in the right eye of Lewis rats by laser photocoagulation (two treatments, 7 days apart) of episcleral and limbal veins. Left eye did not receive laser treatment and served as control. Animals were injected with cobra venom factor every fifth day starting day 7 after first laser, to deplete the complement system. Animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 34 publications
0
52
0
7
Order By: Relevance
“…In both cases, macrophage recruitment into the retina and BRB disturbances occur (Bhattacherjee et al, 1983;McMenamin and Crewe, 1995;Golubnitschaja et al, 2002;Grieshaber and Flammer, 2007), accompanied by degeneration of RGCs (Quigley, 1999;El-Remessy et al, 2008). In addition, glaucoma-linked activation of the complement cascade has also been shown to induce both synaptic loss and apoptosis (Stevens et al, 2007;Jha et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In both cases, macrophage recruitment into the retina and BRB disturbances occur (Bhattacherjee et al, 1983;McMenamin and Crewe, 1995;Golubnitschaja et al, 2002;Grieshaber and Flammer, 2007), accompanied by degeneration of RGCs (Quigley, 1999;El-Remessy et al, 2008). In addition, glaucoma-linked activation of the complement cascade has also been shown to induce both synaptic loss and apoptosis (Stevens et al, 2007;Jha et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Significant deposition of MAC was found in glaucomatous RGCs in human eyes and in experimental models of glaucoma (Kuehn et al 2006;Jha et al 2011;Howell et al 2013). Drug inhibition of complement activation reduced MAC deposition and apoptosis of RGCs in a rat model of glaucoma (Jha et al 2011). Furthermore, C5-deficient DBA/2J mice showed reduced neurodegeneration compared with C5-sufficient DBA/2J mice (Howell et al 2013 Figure 5.…”
Section: Neuroinflammation In Glaucomamentioning
confidence: 99%
“…Especially several experimental studies indicated a neuroprotective potential of β-crystallin B2 when it comes to neuronal impairment in vivo and in vitro [3032]. Concerning the crystallin function, a conclusive mode of action could not be revealed yet [26, 33, 34]. Thus, crystallins might function as critical modulators in the course of glaucoma and might be integral to glaucomatous neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%